RATIONAL PHARMACOTHERAPY IN CARDIOLOGY: FROM ROUTINE CONTROL TO EFFECTIVE MANAGEMENT - N. А. Nikolayev; Y. P. Skirdenko; S. S. Bunova; A. V. Ershov (Рациональная фармакотерапия в кардиологии, 2017)
Aim. To study the clinical effectiveness of patient-oriented therapy in polymorbid patients with arterial hypertension (HT) in comparison with the conventional therapy by the assessment of rationality (secondary combined endpoint) and total mortality (primary endpoints).Material and methods. Dynamics of rationality and total mortality were evaluated in a circular prospective study in 1000 polymorbid patients with HT under patient-oriented or conventional therapies.Results. The strategy of patient-oriented therapy demonstrated a statistically significant advantage over conventional therapy by the criterion of the secondary  combined endpoint, starting from 24 week (Student's t-test: p=0.049 at the 50th and 100th weeks; p=0.002 at the 150th week; p=0.004 at the 200th week). By the end of the study in the patient-oriented group, a positive trend in rationality indicators was achieved in the absolute majority of respondents, while in the conventional therapy group the majority of the baseline parameters changed insignificantly.The total mortality rate in the group of conventional therapy showed a trend of outstripping growth compared with the patient-oriented therapy group, starting from the 50th week of the study. This growth trend was maintained until the end of the study and was of an exponential nature.Differences in total mortality in the samples were statistically significant. A strong correlation was found between the increase in "rationality" indices and the decrease in total mortality.Conclusion. The approach based on management of treatment by criterion of rationality, demonstrated an opportunity of increase in efficiency of treatment, including a reduction in total mortality without the involvement of additional resources and medical interventions.